Assessing the Effect of High Performance Inulin Supplementation via KLF5 mRNA Expression in Adults with Type 2 Diabetes: A Randomized Placebo Controlled Clinical Trail - Abed Ghavami; Neda Roshanravan; Shahriar Alipour; Meisam Barati; Behzad Mansoori; Faezeh Ghalichi; Elyas Nattagh- Eshtivan; Alireza Ostadrahimi (Advanced Pharmaceutical Bulletin, 2018)
Purpose: The worldwide prevalence of metabolic disorders such as diabetes is increasing rapidly. Currently, the complications of diabetes are the major health concern. The aim of this study was to investigate the effect of high performance (HP) inulin supplementation on glucose homeostasis via KLF5 mRNA expression in adults with type 2 diabetes. Methods: In the present clinical trial conducted for a duration of 6 weeks, 46 volunteers diabetic patients referring to diabetes clinic in Tabriz, Iran, were randomly assigned into intervention (n= 23, consuming 10 gr/ d HP inulin) and control groups (n= 23, consuming 10 gr/ d starch). We assessed glycemic and anthropometric indices, blood lipids and plasmatic level of miR-375 as well as KLF5 mRNA expression before and after the intervention. Results: Findings indicated that inulin supplementation significantly decreased fasting plasma glucose (FPG) in comparison to the placebo group (P<0.001). Also Intra-group and between group results showed that inulin supplementation resulted in significant decrease in KLF5 mRNA expression in peripheral blood mononuclear cells (PBMCs) (Fold change: 0.61± 0.11; P-value= 0.001) and significant increase in plasmatic level of miR-375 (Fold change: 3.75± 0.70; P-value=0.004). Conclusion: Considering the improvements of FPG level in diabetic patients, it seems that HP inulin supplementation may be beneficial in controlling diabetes via the expression of some genes. However, further studies are needed to achieve concise conclusions.